UKBM Based Assessment Study (Independent Learning Activity Unit) Biology in Malang City High School (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
UKBM is a small learning unit based on basic competency-based textbooks. The preparation is done sequentially from the easiest to the most difficult to help students learn independently and achieve learning mastery. The research aims to (1) determine the characteristics of the UKBM compiled, (2) describe the preparation and development of UKBM, (3) analyze the development of UKBM-based assessment components, and (4) find obstacles, problems, and solutions for teachers in developing UKBM-based assessment components for Biology High School in Malang City. This research is qualitative descriptive research at State High School in Malang City. The data is primary data from interviews with 5 Biology teachers and secondary data from UKBM scores and documents. The instruments used were interviews, observation, and documentation guidelines. The characteristics of UKBM Biology at State High School in Malang City are in accordance with the characteristics of UKBM guidelines. The preparation and development by the Principal who represents the school in training, then developed by teachers and MGMP that adjusted in each school. Obstacles to implementing UKBM are (1) the emergence of heterogeneous groups in the classroom based on the ability to accelerate UKBM implementation and (2) requiring team teaching and extra effort given that student learning acceleration is different and learning infrastructure adjustment to learning progress and needs.